Predictors of leaving nursing care: a longitudinal study among Swedish nursing personnel. Issue 3 (23rd February 2006) - Fochsen, G; Josephson, M; Hagberg, M; Toomingas, A; Lagerström, M
Abstract : Objectives: Despite extensive research on turnover among nursing personnel very little is known about the impact of physical workload and health on leaving. The aim of this study was to find predictors for leaving nursing care with special reference to physical working conditions and musculoskeletal problems. Methods: This study is based on longitudinal data from a survey of nursing personnel who were employed at various county hospitals in Sweden from 1992–95. A self administrated follow up questionnaire was used to identify their present position in the labour market. The response rate was 73% (n = 1095). Results: The results showed that nursing personnel reporting musculoskeletal problems of the neck/shoulder or knees and those who had limited use of transfer devices were more likely to leave nursing care. Conclusions: The study highlights the importance of taking musculoskeletal problems and use of transfer devices into consideration in order to retain nursing personnel.